A state-of-the-art review on the application of heat pipe system in data centers. (25th November 2021) - Ling, Li; Zhang, Quan; Yu, Yuebin; Liao, Shuguang
Highlights: The necessity and uniqueness of heat pipe system for data centers are discussed. The heat transfer mechanism and impact factors analysis of heat pipe system is discussed. The energy efficiency and environmental analyses of heat pipe system are summarized. The challenges, opportunities and the future of the technology were discussed. Abstract: There has been a continuous increase in the number and size of data centers because of the rapid development in the demand for data storage, networking, and computation. Electricity consumption for a conventional mechanical cooling system employed at a data center compromises approximately 30%–50% of the total energy consumption. A heat pipe system that has the advantages of high thermal efficiency, reliability, and cost effectiveness is considered promising for data center applications to reduce the energy consumption of cooling systems. This study provides a systematic review of existing heat pipe systems applied in data centers. To this end, we limit our review and discussion to the most important and related aspects, which include heat pipe system types, thermal characteristics analysis, and energy efficiency comparison. The heat transfer mechanism of the heat pipe system is described from the perspective of the evaporator and condenser. Further, the effects of the working fluid type, working fluid filling ratio, geometrical parameters, and operational parameters on the thermal performance of the heat pipe system are discussed. The energy efficiency and environmental analysis of an independent heat pipe system and an integrated system with a heat pipe were investigated. The challenges, opportunities, and future of the technology are discussed. This review is expected to contribute significantly to achieve green, sustainable, and energy-saving data centers.